Taking a Look Beneath the Surface: Multicopter UAV-Based Ground-Penetrating Imaging Radars - Grathwohl, Alexander; Stelzig, Michael; Kanz, Julian; Fenske, Patrick; Benedikter, Andreas; Knill, Christina; Ullmann, Ingrid; Hajnsek, Irena; Moreira, Alberto; Krieger, Gerhard; Vossiek, Martin; Waldschmidt, Christian (IEEE Microwave Magazine, 2022)
The field of multicopter unmanned aerial vehicles (UAVs) has seen massive technological advances and decreasing costs over the last decade. Due to the higher prevalence and availability of these multicopter UAVs, there have also been rapid improvements in the software interfaceability, enabling the easy integration of custom software for flight planning and controllers. This opened up completely new possibilities, such as low-cost individual aerial photography, the most common civilian application. Furthermore, lightweight multicopters became widely accessible to the public, boosting the development of UAVs even more.<br